Nine - Dekker, Rachelle (Revell, a division of Baker Publishing Group, 2020)
"A young woman trying to escape her past collides with a girl trying to escape her future, both carrying secrets they're terrified to share. Can they abandon it all-secrets, past, and future-for the freedom they've been offered?"--